Diagnostic Value of Computed Tomography in Gallbladder Perforation - Akıncı, Özlem (Cerrahpaşa Medical Journal, 2023)
Objective: Preoperative diagnosis of gallbladder perforation is difficult; some cases are still diagnosed intraoperatively. In this study, we aimed to research the value of computed tomography findings in gallbladder perforation diagnosis. Methods: Eighty-nine patients who underwent emergency cholecystectomy with the diagnosis of acute cholecystitis or gallbladder perforation between 2018 and 2022 were evaluated retrospectively. Multidetector computed tomography scan findings of all patients were examined by a radiol- ogy specialist. Demographic, clinical data, and computed tomography findings were statistically compared between the perforated group (n = 19) and the nonperforated group (n = 72). Results: In the diagnosis of gallbladder perforation, the positive predictive value of computed tomography was 100%, the negative predictive value was 97.2%, sensitivity was 89.4%, and specificity was 100%. The mean age and the incidence of chronic obstructive pulmonary disease were significantly higher in the perforated group (P < .05). In the computed tomography findings related to the gallbladder, gallbladder wall thickening, pericholecystic fluid collection, abscess/biloma, pericholecystic free air, intraluminal gas, and wall defect findings were observed to be significantly higher in the perforated group (P < .05) In the computed tomography findings related to extra-gallbladder organ, free intraperitoneal fluid and ileus, were significantly more common in the perforated group (P < .05). Conclusion: Multidetector Computed Tomography (MDCT)has high sensitivity, specificity, and predictive value in the diagnosis of gallbladder perfora- tion. Wall defect, increased wall thickening, pericholecystic free fluid or air, abscess or biloma, intraluminal gas, free intraperitoneal fluid, and ileus are significant computed tomography findings in the diagnosis of gallbladder perforation. Cite this article as: Akıncı Ö. Diagnostic value of computed tomography in gallbladder perforation. Cerrahpaşa Med J. 2023;47(2): 197-201.